Exploring Students’ Perspectives on Efclusda Program in Enhancing Speaking Skill - Zuhroh, Nur Elvinatuz; Imaniar, Fahmy; Susanti, Effi (PROJECT (Professional Journal of English Education), 2026)
This research explores students’ views on EFCLUSDA (English Fun Club Matsanisda), an extracurricular English program at MTsN 1 Sidoarjo, and its contribution to improving their speaking skills. The study used a qualitative approach, with data collected through semi-structured interviews involving active participants of the program. The findings show that students consider EFCLUSDA effective when it provides practical, interactive, and student-centered activities within a supportive environment. They also highlighted the importance of varied tasks, the use of technology, and guidance from mentors to make speaking practice more meaningful. These insights indicate that EFCLUSDA plays an important role in helping students build fluency and confidence, while also giving schools direction in designing programs that respond to students’ needs. The study further suggests that integrating students’ perspectives into program design is essential for the success of English learning. In addition, practical recommendations such as increasing opportunities for speaking practice, using diverse themes, and inviting guest speakers can strengthen the program’s impact.